Curcumin: A Potential Detoxifier Against Chemical and Natural Toxicants - Kumar, Harsh; Dhalaria, Rajni; Kimta, Neetika; Guleria, Shivani; Upadhyay, Navneet Kumar; Nepovimova, Eugenie; Dhanjal, Daljeet Singh; Sethi, Nidhi; Manickam, Sivakumar (Phytotherapy research, 2025)
The human body gets exposed to a variety of toxins intentionally or unintentionally on a regular basis from sources such as air, water, food, and soil. Certain toxins can be synthetic, while some are biological. The toxins affect the various parts of the body by activating numerous pro-inflammatory markers, like oxidative stresses, that tend to disturb the normal function of the organs ultimately. Nowadays, people use different types of herbal treatments, viz., herbal drinks that contain different spices for detoxification of their bodies. One such example is turmeric, the most commonly available spice in the kitchen and used across all kinds of households. Turmeric contains curcumin, which is a natural polyphenol. Curcumin is a medicinal compound with different biological activities, such as antioxidant, antineoplastic, anti-inflammatory, and antibacterial. Hence, this review gives a comprehensive insight into the promising potential of curcumin in the detoxification of heavy metals, carbon tetrachloride, drugs, alcohol, acrylamide, mycotoxins, nicotine, and plastics. The review encompasses diverse animal-based studies portraying curcumin's role in nullifying the different toxic effects in various organs of the body (especially the liver, kidney, testicles, and brain) by enhancing defensive signaling pathways, improving antioxidant enzyme levels, inhibiting pro-inflammatory markers activities and so on. Furthermore, this review also argues over curcumin's safety assessment for its utilization as a detoxifying agent.
Keywords: Oxidative Stress; Metals, Heavy; in vivo; oxidační stres; herbal drugs; Humans; detoxification; curcumin; health; lidé; Antioxidants; zvířata; toxicity; Curcuma; kurkumin; antioxidancia; Curcumin; těžké kovy; Animals